How prosocial is moral courage?. (April 2022) - Sasse, Julia; Li, Mengyao; Baumert, Anna
Abstract: Moral courage, that is, defending moral beliefs despite personal risks, is often seen as a hallmark of prosocial behavior. We argue that prosociality in moral courage is, however, complex. While its prosociality is often evident at a higher societal level, it can be contested in some aspects of morally courageous acts. We review the literature on two such aspects and highlight that differences and conflicts in moral beliefs, as well as the confrontational nature of many morally courageous acts, call into question prosociality. We recommend that future research takes the complexity of prosociality in moral courage into account to obtain a comprehensive and nuanced understanding of the psychological underpinnings of moral courage and its contributions to the functioning of societies.